Nestor lima e a modernização conservadora da gestão educacional no Rio Grande do Norte entre 1924-1928 - Ramos, Jane Karoline Carvalho de Aguiar (2009)
This study attempts to investigate the school administration in the Department of Education of Rio Grande de Norte, in the period 1924 to 1928, in the context of conservative modernization in its management, implemented by Nestor Lima dos Santos. Addresses the trends of administrative Nestor Santos Lima and sequence of these variables so that we can correlate and monitor the development of various economic, social, cultural and political, to show how influenced and even determined the direction of education, not only the state of RN, but throughout the country. For this purpose, it is the recapitulation of the history of life, experiences of work and travel reports of this important figure, including administrative concepts, aiming to identify the school administration, introduced by him in the 1920s, as those who received influence of characters that included the social and historical context of the time, reconstituting the ways following the education. It was developed by Nestor shares in Lima on the administration of public schools, their way of management, and can see how was the process of modernization of education in Rio Grande do Norte state and how it followed the rapid changes, experienced by Brazil, during this period. Show up on the design aspects of modernizing Nestor Lima in the Department of Education, the Director General of Administrative Acts, the internal record of school groups, Isolated Schools, Schools rudimentary and the newly created Board of Education, highlighting the Internal Rules of Council but the General Regulations of the Department of Education. This work also highlights the proposed administrative Nestor of Lima, while educational model of an operating system of the organization, training and education, which is present in the area of production of discourse, through body practice, characteristic of the record established levels of policy development and implementation of educational instruction in all state. Key-words: school administration. Conservative modernization. Public Education